2021
DOI: 10.1002/anie.202014981
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Coordinative Binding of O2 at the Active Center of a Copper‐Dependent Enzyme

Abstract: Molecular oxygen (O2) is a sustainable oxidation reagent. O2 is strongly oxidizing but kinetically stable and its final reaction product is water. For these reasons learning how to activate O2 and how to steer its reactivity along desired reaction pathways is a longstanding challenge in chemical research.[1] Activation of ground‐state diradical O2 can occur either via conversion to singlet oxygen or by one‐electron reduction to superoxide. Many enzymes facilitate activation of O2 by direct fomation of a metal‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…FGE binds a specific peptide cysteine residue of sulfatases and some phosphatases to form trigonal planar tris thiolate Cu­(S Cys ) 2 (peptide-CH 2 S) (Figure ), which initiates O 2 activation and transforms the cysteine residue into formylglycine (fGly) (Scheme ). It is noteworthy to mention that fGly upon 1,2-addition of water produces fGly-geminal diol, which acts as a catalytic nucleophile of hydrolytic enzymes, sulfatases, that cleave sulfate esters to sulfates/hydrogensulfates (Scheme S1). So, dysfunction of FGE in humans builds up sulfate esters (known as multiple sulfatase deficiency), an excess of which can cause the death of the brain, skeletal, and skin cells …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…FGE binds a specific peptide cysteine residue of sulfatases and some phosphatases to form trigonal planar tris thiolate Cu­(S Cys ) 2 (peptide-CH 2 S) (Figure ), which initiates O 2 activation and transforms the cysteine residue into formylglycine (fGly) (Scheme ). It is noteworthy to mention that fGly upon 1,2-addition of water produces fGly-geminal diol, which acts as a catalytic nucleophile of hydrolytic enzymes, sulfatases, that cleave sulfate esters to sulfates/hydrogensulfates (Scheme S1). So, dysfunction of FGE in humans builds up sulfate esters (known as multiple sulfatase deficiency), an excess of which can cause the death of the brain, skeletal, and skin cells …”
Section: Introductionmentioning
confidence: 99%
“… (b) Substrate-bound FGE from Thermomonospora curvata (PDB: 6S07). Color code: C, gray; N, blue; O, red; S, yellow; Cu, pink.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former is helpful for understanding the reaction process, and the latter improves the reaction efficiency. Currently, copper catalysts are commonly known as the contribution to efficient oxygen activation. However, the large size, non-uniform dispersion, and unclear bonding with the substrate altogether lead to the disadvantages of low selectivity and low conversion efficiency in the process of oxygen activation. , Based on this, the preparation of a single Cu atom catalyst is expected as a portable strategy to activate O 2 with high efficiency. In addition, previous research studies have shown that two-dimensional layered structures generally have excellent photocatalytic performance in the production of 1 O 2 . This results from the fact that the two-dimensional confined layered structure leads to a strong Coulomb interaction between electrons and holes, which is conducive to the production of more excitons, then resulting in more 1 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…35−40 However, the large size, non-uniform dispersion, and unclear bonding with the substrate altogether lead to the disadvantages of low selectivity and low conversion efficiency in the process of oxygen activation. 41,42 Based on this, the preparation of a single Cu atom catalyst is expected as a portable strategy to activate O 2 with high efficiency. In addition, previous research studies have shown that twodimensional layered structures generally have excellent photocatalytic performance in the production of 1 O 2 .…”
Section: Introductionmentioning
confidence: 99%